Weather parameters and nosocomial bloodstream infection: a case-referent study - Caldeira, Silvia Maria [UNESP]; Cunha, Antonio Ribeiro da [UNESP]; Akazawa, Renata Tamie [UNESP]; Moreira, Rayana Gonçalves [UNESP]; Souza, Lenice do Rosário de [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP] (FapUNIFESP (SciELO), 2015)
Objective: To evaluate if temperature and humidity influenced the etiology of bloodstream infections in a hospital from 2005 to 2010. Methods: The study had a case-referent design. Individual cases of bloodstream infections caused by specific groups or pathogens were compared with several references. In the first analysis, average temperature and humidity values for the seven days preceding collection of blood cultures were compared with an overall “seven-days moving average” for the study period. The second analysis included only patients with bloodstream infections. Several logistic regression models were used to compare different pathogens and groups with respect to the immediate weather parameters, adjusting for demographics, time, and unit of admission. Results: Higher temperatures and humidity were related to the recovery of bacteria as a whole (versus fungi) and of gram-negative bacilli. In the multivariable models, temperature was positively associated with the recovery of gram-negative bacilli (OR = 1.14; 95%CI 1.10;1.19) or Acinetobacter baumannii (OR = 1.26; 95%CI 1.16;1.37), even after adjustment for demographic and admission data. An inverse association was identified for humidity. Conclusions: The study documented the impact of temperature and humidity on the incidence and etiology of bloodstream infections. The results correspond with those from ecological studies, indicating a higher incidence of gram-negative bacilli during warm seasons. These findings should guide policies directed at preventing and controlling healthcare-associated infections.

Objetivo: Avaliar se temperatura e umidade influenciam a etiologia das infecções na corrente sanguínea em hospital, no período de 2005 a 2010. Métodos: O estudo teve delineamento caso-referência. Casos individuais de infecções de corrente sanguínea por patógenos ou grupos de interesse foram comparados com diferentes referências. Na primeira etapa, valores médios de temperatura e umidade, para os sete dias que precederam a coleta de culturas de sangue, foram comparados com a “média-móvel de ordem 7” para todos os dias do período do estudo. A segunda etapa incluiu somente os casos com culturas positivas. Foram realizadas análises por regressão logística para avaliar a influência dos parâmetros meteorológicos imediatos sobre a etiologia dessas infecções, ajustando os resultados para dados demográficos, tempo e unidade de internação. Resultados: Temperatura e umidade mais elevadas foram associadas às infecções de corrente sanguínea causadas por bactérias como um todo (versus fungos) e por bacilos Gram-negativos. Nos modelos multivariados, a temperatura foi positivamente associada com o isolamento nas culturas de bacilos Gram-negativos (OR = 1,14; IC95% 1,10;1,19) ou A. baumannii (OR = 1,26; IC95% 1,16;1,37), mesmo após ajuste para dados demográficos e de internação. Associação inversa foi identificada por umidade. Conclusões: O estudo documentou o impacto de temperatura e umidade sobre incidência e etiologia de infecções da corrente sanguínea. Os resultados são coerentes com os relatados em estudos ecológicos, apontando para maior incidência de bacilos Gram-negativos durante as estações quentes. Esses achados devem orientar as estratégias direcionadas à prevenção e controle de infecções relacionadas à assistência à saúde.
Parâmetros meteorológicos e infecção hospitalar de corrente sanguínea: estudo caso-referência
Keywords: Cross infection, etiology; Temperature; Humidity; Bacterial infections and mycoses, microbiology; Infecção hospitalar, etiologia; Temperatura ambiente; Umidade; Infecções bacterianas e micoses, microbiologia